Monitoring subcontracting in a suppliers' hierachy - Cella, M (University of Oxford, 2005)
In this paper we study the delegation of a production process in a three-tier hierarchy. The principal contracts directly only with the supplier that produces the first input leaving him in charge of the contract for the production of the second input. We allow the principal to costlessly monitor the communication between the agents at the subcontracting stage in an attempt to save on informational rents and improve productive efficiency. We show that, if the contractor is free to choose the type of subcontract, he must be given additional incentives to acquire information about the subcontractor which will then be the object of the monitoring. The monitoring is therefore much less effective then when the principal can force the contractor into choosing her preferred subcontract.